2016
DOI: 10.3892/ol.2016.5535
|View full text |Cite
|
Sign up to set email alerts
|

JS-K promotes apoptosis by inducing ROS production in human prostate cancer cells

Abstract: Reactive oxygen species (ROS) are chemical species that alter redox status, and are responsible for inducing carcinogenesis. The purpose of the present study was to assess the effects of the glutathione S transferase-activated nitric oxide donor prodrug, JS-K, on ROS accumulation and on proliferation and apoptosis in human prostate cancer cells. Cell proliferation and apoptosis, ROS accumulation and the activation of the mitochondrial signaling pathway were measured. The results demonstrated that JS-K may inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…A number of researchers noted that excessive ROS was the cause of apoptosis. [35][36][37][38] Daniel et al found that the death of bacteria induced by antibiotics displayed the same physiological and biochemical characteristics as apoptosis. 39 Other scholars also observed the morphological changes and biochemical reactions related to apoptosis in prokaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers noted that excessive ROS was the cause of apoptosis. [35][36][37][38] Daniel et al found that the death of bacteria induced by antibiotics displayed the same physiological and biochemical characteristics as apoptosis. 39 Other scholars also observed the morphological changes and biochemical reactions related to apoptosis in prokaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there are several reports on the relationship between ROS production and treatment efficacy in prostate cancer. For example, treatment with JS-K, a glutathione S transferase-activated nitric oxide donor prodrug, for 24 h, increased the proportion of apoptotic cells, by inducing ROS production in prostate cancer cells (22RV1, C4-2, LNCaP, and PC-3) [ 140 ]. Interestingly, these authors also showed that the pro-apoptotic effect of JS-K is dose-dependent, and 22RV1 and C4-2 cells were more sensitive than LNCaP and PC-3 cells [ 141 ].…”
Section: Apoptosis and Rosmentioning
confidence: 99%
“…Reactive oxygen species (ROS) play essential roles in maintaining biological functions such as cell proliferation and apoptosis [ 17 ]. The moderation of intracellular ROS levels can promote cell proliferation and differentiation, and the overproduction of ROS can lead to cytotoxicity in cancer cells [ 18 , 19 ]. There is evidence that MAPK and STAT3 are representative ROS-responsive signaling pathways that are involved in mitochondrial dysfunction and cell survival [ 20 ].…”
Section: Introductionmentioning
confidence: 99%